PEMANFAATAN HIJAUAN RAWA TERMODIFIKASI SEBAGAI PAKAN LENGKAP GRANULE TERHADAP KARKAS DAN DAGING KAMBING LOKAL - Jaelani, Achmad; Zakir, Muhammad Irwan (Universitas Djuanda Bogor, 2020)
Swamps forage generally have crude fiber content and tannin content which is quite high. Unlike the case with legumes which are high in protein content but crude fiber content, and tannins that are not too high compared to swamp forages. The presence of tannin in swamp forage, has an impact on palatability, digestibility and biological value of feed. In such a situation, modification of swamp forages with tree legumes is a promising alternative source of feed for goats. Protein in small ruminant animals is generally degraded in the rumen before reaching the abomasum, where absorption of nutrients occurs. As a result, protein digestibility will be reduced because it is damaged during the journey to the abomasum, so there needs to be modification so that protein damage to the rumen can be reduced. One way is to create a protein protector that is able to protect protein by using tannin which is quite abundant in swamp forages. In addition to functioning as a protein protector, tannin is also useful as an anthelmintic agent (anti-parasite) in goats, so that it will reduce the occurrence of worm disease in goats so that it will reduce the use of worm parasitic drugs which will have an impact on goat performance. The specific objectives of this study were to analyze the ability of a combination of swamp forage with modified legume as a complete feed granule with different tannin content on the quality of local carcass and goat meat Trial feeding was carried out on 12 male local goats aged 1.5-2 years, body weight 33-35 kg. At this stage a modified swamp and legume forage in the form of granules was modified as a complete feed on the performance of local meat-producing goats. Parameters measured included: Carcass quality, physical and organoleptic quality of meat. The results showed that the application of swamp forage and indigofera legume on male goats affected the cut weight and carcass percentage. Giving a combination of swamp forage with indigofera legume with different tannin content affects the physical properties of goat meat which includes cooking losses, water holding capacity, but does not affect the tenderness of meat, and pH.